Luminescence properties of NaAIP₂O₇ crystals doped with chromiumions - Gomenyuk, O.V.; Nedilko, S.G.; Stus, N.V.; Slobodyanyk, M.S.; Scherbatsky, V.P. (Functional Materials, 2004)
Luminescence properties of NaAIP₂O₇ crystals doped with chromium ions have been investigated. Luminescence spectra of these crystals consist of two main bands in the green-orange and red spectral regions, respectively. Positions and shapes of the bands depend on the sample temperature, concentration of the impurity ions, and excitation wavelength. Complex structure of the green-orange band is caused by a superposition of matrix intrinsic radiation and emission of the distorted CrO₄²⁻ groups, where chromium ion has 6+ charge. The red luminescence band was assigned to electron transition in the Cr³⁺ ions located in the octahedral oxygen environment. A special attention has been paid to discuss the possibility for chromium ions arrangement in different positions of the crystal lattice.